2020
DOI: 10.1172/jci132184
|View full text |Cite
|
Sign up to set email alerts
|

Taxane resistance in prostate cancer is mediated by decreased drug-target engagement

Abstract: and intricate microtubule network into dense microtubule bundles that can be readily visualized by fluorescence microscopy. Microtubules are highly dynamic filaments fulfilling a number of functions in interphase, such as intracellular trafficking and signaling. They are also critically involved in the formation of the mitotic spindle that facilitates chromosome segregation during mitosis, so that taxane treatment results in aberrant mitotic arrest and apoptotic cell death (5). Although this mitotic arrest is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 41 publications
1
29
0
2
Order By: Relevance
“…Some have suggested that cancer cells recognize a stress signal following taxane treatment and respond with upregulating isotypes of tubulin that allow them to increase MT dynamics, upregulate survival signaling pathways, or evade forced apoptosis [ 339 ]. One study quantified the amount of polymerized and stable MTs that self-arrange in clumps or bundles, known as MT bundling, that occurs in taxane-sensitive or taxane-resistant tumors following treatment [ 340 , 341 ]. The amount of bundling was then correlated with the documented responsiveness of the patient to therapy, where decreased bundling was observed in patients that had recorded resistance to therapy.…”
Section: Taxane Resistance In Prostate Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Some have suggested that cancer cells recognize a stress signal following taxane treatment and respond with upregulating isotypes of tubulin that allow them to increase MT dynamics, upregulate survival signaling pathways, or evade forced apoptosis [ 339 ]. One study quantified the amount of polymerized and stable MTs that self-arrange in clumps or bundles, known as MT bundling, that occurs in taxane-sensitive or taxane-resistant tumors following treatment [ 340 , 341 ]. The amount of bundling was then correlated with the documented responsiveness of the patient to therapy, where decreased bundling was observed in patients that had recorded resistance to therapy.…”
Section: Taxane Resistance In Prostate Cancermentioning
confidence: 99%
“…In fact, studies have demonstrated that cells derived from DTX-treated CRPC patients lack AR nuclear localization and that MTs directly bind to AR [ 348 , 349 , 350 ]. There is evidence that the amount of nuclear localization of AR negatively correlates with clinical responsiveness to taxane treatment, where cytoplasmic sequestration of AR is associated with increased MT bundling and increased response to taxanes [ 341 , 351 ]. Likewise, there is a connection between DTX resistance and increased AR signaling [ 335 ], indicating an association between taxane efficacy and the AR signaling pathway mediated by MTs.…”
Section: Taxane Resistance In Prostate Cancermentioning
confidence: 99%
“…Taxanes, belonging to a class of diterpenes with antineoplastic effects, are plant alkaloids. They are microtubule-stabilizing compounds that inhibit mitosis of cancer cells and interfere with a number of biochemical pathways to induce apoptosis and cancer cell death [ 34 , 35 ]. Among all the classes of antineoplastic agents, taxanes are one of the most widely used representing a cornerstone of chemotherapy.…”
Section: Oncologic Treatment Related Cardiotoxicity: the Role Of Omentioning
confidence: 99%
“…1,2 However, patients may develop severe complications, iatrogenic injury, drug toxicity, and therapy resistance. 3,4 Castration-resistant PCa (CRPC) is considered the terminal stage of the disease, 5 and prolonging the occurrence of castration-resistant malignancy remains therapeutically challenging. Gene therapy has been deployed to deliver specific nucleotide sequences to target cells, where they can correct or compensate for the existing gene defect or abnormality that leads to specific diseases or inhibit the expression of oncoproteins.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 However, patients may develop severe complications, iatrogenic injury, drug toxicity, and therapy resistance. 3 , 4 …”
Section: Introductionmentioning
confidence: 99%